Incidence rate and pattern of clinically relevant potential drug-drug interactions in a large outpatient population of a developing country - Ehsan Nabovati; Hasan Vakili-Arki; Zhila Taherzadeh; Mohammad Reza Saberi; Ameen Abu-Hanna; Saeid Eslami (Wolters Kluwer Medknow Publications, 2016)
The objective of this study was to determine incidence rate, type, and pattern of clinically relevant potential drug-drug interactions (pDDIs) in a large outpatient population of a developing country. A retrospective, descriptive cross-sectional study was conducted on outpatients' prescriptions in Khorasan Razavi province, Iran, over 12 months. A list of 25 clinically relevant DDIs, which are likely to occur in the outpatient setting, was used as the reference. Most frequent clinically relevant pDDIs, most common drugs contributing to the pDDIs, and the pattern of pDDIs for each medical specialty were determined. Descriptive statistics were used to report the results. In total, out of 8,169,142 prescriptions, 6,096 clinically relevant pDDIs were identified. The most common identified pDDIs were theophyllines-quinolones, warfarin-nonsteroidal anti-inflammatory drugs, benzodiazepines-azole antifungal agents, and anticoagulants-thyroid hormones. The most common drugs contributing to the identified pDDIs were ciprofloxacin, theophylline, warfarin, aminophylline, alprazolam, levothyroxine, and selegiline. While the incidence rate of clinically relevant pDDIs in prescriptions of general practitioners, internists, and cardiologists was the highest, the average pDDI incidence per 10,000 prescriptions of pulmonologists, infectious disease specialists, and cardiologists was highest. Although a small proportion of the analyzed prescriptions contained drug pairs with potential for clinically relevant DDIs, a significant number of outpatients have been exposed to the adverse effects associated with these interactions. It is recommended that in addition to training physicians and pharmacists, other effective interventions such as computerized alerting systems and electronic prescribing systems be designed and implemented.